2020
DOI: 10.1002/tbio.201900026
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence visualization of the borders of bladder tumors after TUR with quantitative determination of diagnostic contrast

Abstract: The study demonstrates the ability of fluorescence diagnosis to perform intraoperative analysis of the bladder wall. The data of 10 patients with superficial bladder cancer who underwent PDD with the use of the fluorescence video system with excitation wavelenght in the “red” wavelength range and TUR is discussed. General condition of the bladder is assessed, the main foci of the tumor are determined. Then a tumor resection is performed. Further examination and identification of the fluorescing boundaries of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Further examination and identification of the fluorescing boundaries of the tumor remaining after TUR are performed to make a decision of a re-resection. In addition, small fluorescing tumor foci, not detected with white light cystoscopy, can be detected [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further examination and identification of the fluorescing boundaries of the tumor remaining after TUR are performed to make a decision of a re-resection. In addition, small fluorescing tumor foci, not detected with white light cystoscopy, can be detected [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The peak wavelength of the laser (635 nm) was chosen as the best trade-o (i) using only one fluorescence excitation light source; (ii) extending tissue dep (compared to blue light excitation); and (iii) enabling the detection of three d (Ce6, PpIX, and MB). Regarding Ce6, despite its second main absorption pea gion of 660 nm, its molar extinction at 635 nm is still about 5000 cm −1 /M (whic The imaging system has already been tested in clinical settings and has shown that it detects fluorescence in real conditions with sufficient sensitivity [29,30]. In the present work, the experiment was designed to be as close as possible to the picture obtained in real conditions.…”
Section: Bimodal Endoscopic System and Image Acquisition Protocolmentioning
confidence: 94%
“…A bimodal video system with a rigid endoscope featuring a 45-degree bevel was used for image acquisition. The main technical features of this device, developed by our team, are provided in [29,30]. Briefly, it consists of two cameras (a highly sensitive black-andwhite digital CCD with an optical filter and a color camera), beam splitter, cystoscope, and illuminating devices (WL source, laser).…”
Section: Bimodal Endoscopic System and Image Acquisition Protocolmentioning
confidence: 99%
See 2 more Smart Citations